Besednovrstna kategoriziacija kot slovnični temelj pomenskega opisa v slovarju - Snoj, Jerica (Slovenščina 2.0, 2018)
The paper deals with word-class categorization from the standpoint of providing word-class tags in dictionaries of Slovene at a general level, applicable regardless of the lexicographic concept. We first demonstrate the individuality of word-class categorization in the theory of grammar, followed by the demonstration of the role of word-class categorization of lexical units within the description of meaning in a dictionary. Providing examples for the predicative, particle, and participial compounds, we demonstrate the development of word-class categorization in the existing Slovene dictionaries and provide guidelines for futuredictionaries of Slovene.
Keywords: besedne vrste; besednovrstna kategorizacija; grammar; jezikovni opis; lexicography; linguistic description; meaning; parts of speech; parts of speech categorization; pomen; slovaropisje; Slovene; slovenščina; slovnica